Current data on predictive markers for anti-angiogenic therapy in thoracic tumours - Reinmuth, Niels; Thomas, Michael; Meister, Michael; Schnabel, Philipp Albert; Kreuter, Michael (The European respiratory journal, 2010)
The fact that growth and spread of tumours are dependent on angiogenesis has led to the investigation of the role of anti-angiogenic agents in the therapeutic strategies for thoracic tumours such as nonsmall cell lung cancer or mesotheliomas. Since various angiogenic factors may contribute to the regulation of angiogenesis in the individual tumour, in the era of increasing amounts of clinically tested agents it is of utmost importance to properly select patients that may benefit from a specific therapy. Due to the complex nature of tumour angiogenesis, various biomarkers may be applicable. For example, the profile of activated angiogenic pathways in endothelial cells may be determined in order to make conclusions about the relevance of inhibiting a given pathway by a selected agent. Moreover, changes in protein expression in stromal and tumour cells, as well as structural alterations in the vasculature, may be used for predicting and monitoring the clinical effects of such a therapy. In this review, the current data from clinical studies evaluating predictive markers for anti-angiogenic agents in thoracic cancers are summarised. Besides giving clinical examples, the rationales for investigating various parameters based on pre-clinical studies are described.
Gesehen am 12.05.2023